Successful switch to ofatumumab after liver injury associated with ocrelizumab treatment in multiple sclerosis: a case report - Mariottini, Alice; Barilaro, Alessandro; Lotti, Antonio; Marra, Fabio; Massacesi, Luca (Frontiers in Neurology, 2024)
Drug-induced liver injury (DILI) is a potential adverse event of disease-modifying therapies (DMTs) for the treatment of multiple sclerosis (MS), as well as of methylprednisolone pulsed therapy used in case of MS relapse. DILI may be induced by different mechanisms, including idiosyncratic reaction, autoimmune hepatitis or viral reactivation. In patients receiving the humanized anti-CD20 monoclonal antibody (mAb) ocrelizumab, DILI has been rarely reported and was mostly associated with hepatitis B virus (HBV) reactivation. Here we present the case of a woman with highly active relapsing–remitting MS who had experienced two episodes of DILI while receiving different DMTs, and was successfully switched to ofatumumab, a fully human anti-CD20 mAb, after a further event associated with ocrelizumab treatment and unrelated to HBV reactivation. Despite sharing the mechanism of action, differences in structure, pharmacokinetic/pharmacodynamic profile, and use of ancillary drugs (only needed for ocrelizumab) may have accounted for the successful switch. To our knowledge, this is the first report of a successful switch from ocrelizumab to ofatumumab due to DILI. Ofatumumab may therefore represent a valid therapeutic option for patients experiencing DMTs- and ocrelizumab-induced liver injury, providing that HBV reactivation has been ruled out.